Screening mint (Mentha spp.) accessions against root-knot nematode infection - Patra, Rakesh Pandey, Nirmal Kumar (Journal of Spices and Aromatic Crops, 2001)
Different mint (Mentha spp.) accessions were screened in vitro against root-knot nematode (Meloidogyne incognita). Root-knot infection was high in Siwalik and Himalaya and two M. arvensis cultivars, whereas moderate reaction was found in M. arvensis cultivars like SS-11, SS-27, Gomti, Kosi, M. cardiaca, and MAH-1. The lowest root-knot infection level was found on SS-4, SS-5, Kalka and 55-20. Moderate to high degree of resistance was recorded in SS-1-4, SS-2-7, SS-15, SS-26, M. piperita cv. Kukrail, M. spicata cv. Neera, M. spicata cv. Arka, M. sitrata cv. Kiran, M. gracilis and M. viridis.